2002
DOI: 10.1074/jbc.m102188200
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splice Variants of α7β1Integrin Selectively Recognize Different Laminin Isoforms

Abstract: The integrin ␣ 7 ␤ 1 occurs in several cytoplasmic (␣ 7A , ␣ 7B ) and extracellular splice variants (␣ 7X1 , ␣ 7X2 ), which are differentially expressed during development of skeletal and heart muscle. The extracellular variants result from the alternative splicing of exons X1 and X2, corresponding to a segment within the putative ligand binding domain. To study the specificity and affinity of the X1/X2 variants to different laminin isoforms, soluble ␣ 7 ␤ 1 complexes were prepared by recombinant coexpression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 53 publications
5
74
0
Order By: Relevance
“…A high yield expression of soluble ␣ 7 X2␤ 1 integrin was achieved by coexpression of the murine ␣ 7 X2 integrin ectodomain with the human ␤ 1 integrin ectodomain in Drosophila Schneider's cells. Similar to the results of von der Mark et al (28), we showed that soluble ␣ 7 X2␤ 1 integrin bound to laminin-1 and laminin-2/4, but failed to interact with laminin-5. Despite being the major laminin isoform in muscle tissue (11), laminin-2/4 was bound by ␣ 7 X2␤ 1 integrin with a lower affinity than laminin-1.…”
Section: K Dsupporting
confidence: 80%
“…A high yield expression of soluble ␣ 7 X2␤ 1 integrin was achieved by coexpression of the murine ␣ 7 X2 integrin ectodomain with the human ␤ 1 integrin ectodomain in Drosophila Schneider's cells. Similar to the results of von der Mark et al (28), we showed that soluble ␣ 7 X2␤ 1 integrin bound to laminin-1 and laminin-2/4, but failed to interact with laminin-5. Despite being the major laminin isoform in muscle tissue (11), laminin-2/4 was bound by ␣ 7 X2␤ 1 integrin with a lower affinity than laminin-1.…”
Section: K Dsupporting
confidence: 80%
“…On laminin-10/11, HuX2/A cells adhered poorly whereas HuX1/A cells showed strong affinity. von der Mark and collaborators recently showed that soluble double truncated forms of ␣7X1 and ␣7X2 bind differently to various laminin isoforms (von der Mark et al, 2002). Our results are similar in that ␣7X1 expressing cells bound to laminin-10/11 substrates whereas ␣7X2 bound preferentially to laminin-1.…”
Section: Discussionsupporting
confidence: 82%
“…The laminin-binding ␣7␤1 integrin, expressed in mouse skeletal muscle as early as E10.5 d of development, mediates myoblast motility on laminin substrates (Kaufman et al, 1980;Kaufman et al, 1991;Yao et al, 1996a,b;Crawley et al, 1997;von der Mark et al, 2002). In mature skeletal muscle, the ␣7 receptor is associated with costameres and the myotendinous and neuromuscular junctions (Bao et al, 1993;Belkin et al, 1996;Martin et al, 1996;van der Flier et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although laminin-111 is not expressed in normal or dystrophic adult skeletal muscle, studies indicate it is a preferred ligand for ␣ 7 ␤ 1 -integrin (21,22). Treatment with laminin-111 stabilized the sarcolemma of mdx skeletal muscle, reduced myofiber degeneration, decreased serum creatine kinase, and protected muscle from exercise-induced injury, suggesting that treatment with laminin-111 may be a potent therapy for DMD.…”
Section: Discussionmentioning
confidence: 99%